LEADERSHIP THEORIES IN EDUCATION - Mexro’zbek Muxtorjon o’g’li Jo’raboyev; Sultanova Nargiza Xudayberdiyevna (Web of Journals Publishing, 2024)
Exploring leadership theories applicable to educational institutions sheds light on the various frameworks guiding effective leadership in the field of education. Let's delve into key leadership theories relevant to educational settings.